The role of offset stems in revision knee arthroplasty - Baldini, Andrea (Curr Rev Musculoskelet Med, 2015)
Revision total knee arthroplasty (TKA) represents a technically challenging procedure. The use of an offset stem extension can help in addressing some of the difficulties that can be encountered during surgery and, in particular, anatomical mismatch, malalignment, and gap balancing. Different offset stem extensions are available and can be classified according to four parameters: modularity, location of the offset, direction, and size of the displacement. Offset stem extensions can assist with implant alignment on the metaphysis if there is an offset diaphysis, can avoid medial-lateral or anterior-posterior component overhang, can reduce the incidence of coronal or sagittal malalignment, and can help in balancing the flexion and extension spaces by effectively translating the components. The aim of this study is to give an overview of the currently available evidence regarding the use of offset stem extensions in revision TKA as well as some useful surgical tips.